Successful first rehabilitation and release of an endangered Ethiopian wolf - Sandra Lai; Getachew Asefa; Muktar Abute; Girma Eshete; Don‐Jean Léandri‐Breton; Fekede Regassa; Claudio Sillero‐Zubiri; Jorgelina Marino (Conservation Science and Practice)
Abstract Wildlife rehabilitation is widely practiced to help injured animals recover and return to the wild, particularly benefiting endangered species that have small local populations. Here, we report the first case of a rehabilitated Ethiopian wolf that was successfully released back in the Simien Mountains. Through this case study, we documented the clinical treatment provided, recovery, and behavior of this individual during captivity, and post‐release monitoring in the wild using a GPS collar. After 51 days of captivity, during which a bone fracture in the hind leg caused by a gunshot was treated, the wolf was released back. After remaining with his pack members for 22 days, the wolf dispersed and settled in an unoccupied territory, where he paired with a female and successfully sired a litter. This study provides important insights on rehabilitation and post‐release monitoring that will inform conservation management of the Ethiopian wolf.